Influencing factors of academic performance among first-year university students in Malaysia - Pauviya Guna Segar; Azlina Mohd Kosnin; Lina Handayani (Journal of Education and Learning (EduLearn), 2026)
This study investigates the factors influencing academic success among first-year university students in Malaysia during their transition to university. Using qualitative methods, semi-structured interviews were conducted with 15 first- and second-year students to explore their experiences. Thematic analysis identified several key factors affecting academic performance, including family influence, peer relationships, university environment, self-esteem, mental health, study habits, and lifestyle. Positive parenting styles and family support were found to be crucial for academic success, while negative parenting styles, financial difficulties, and lack of parental involvement posed challenges. Supportive peer relationships were linked to enhanced academic outcomes, whereas toxic peer pressure negatively affected performance. A positive university environment, with accessible resources and supportive lecturers, contributed significantly to success. Mental health issues, low self-esteem, and poor study habits, such as procrastination and irregular sleep, had detrimental effects on academic performance. While the study provides valuable insights, it is limited by a small sample size, reliance on subjective self-reports, and a lack of a longitudinal approach. Future research should address these limitations by using larger, diverse samples and incorporating quantitative methods. Additionally, studies should focus on students at risk of underperformance to gain a broader understanding of the factors impacting academic success.